Spiritual care for the mothers of critical newborn hospitalized - Saucedo-Soberon, Luz Milagros (2021)
Objetive: Describe and understand the spiritual care provided to mothers of critically ill infants hospitalized in a public hospital in Chiclayo, Peru. Material and methods: Qualitative descriptive exploratory research; the sample was not probabilistic and the size was determined by the saturation and redundancy technique, being the subjects of study 12 mothers who have their children hospitalized in the Neonatal Intensive Care Unit, and 12 nurses, this allowed triangulating the information; In addition, the data was collected through the in-depth semi-structured interview, then they were processed manually by means of content analysis. Results: a) Recognition of religious beliefs, b) Prayer as the main spiritual resource. Devoted internship facilities, c) Assessment and respect for religious creed. Conclusion: In the neonatology environment, mothers have a lactation room that is decorated with religious symbols such as the Divine Child and the Virgin Mary. Meanwhile, in the neonatal critical care unit, nurses facilitate the entry of different religious leaders. Some mothers leave stamps, rosaries or other religious symbols in incubators according to their culture. Regardless of religion, prayer is the most practiced spiritual resource in this context, since nurses pray at the begging of their work shift or do it afterwards with the mothers, who pray together with their children and in a group. In the study, the majority professed the Catholic religion, but they found as limiting the short time that the have to give greater emphasis to spiritual care.